2015
DOI: 10.2134/agronj14.0549
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Soil Properties after Five Years of No‐Till and Strip‐Till

Abstract: Recent research in Illinois suggests that yield increase in corn (Zea mays L.) and soybean [Glycine max. (L.) Merr.] with strip-till (ST) vs. no-till (NT) could be explained by diff erences in root characteristics and enhanced nutrient uptake in ST. However, the eff ect of these tillage practices on soil properties remains unclear. Our objective was to evaluate the impact of NT and ST on soil organic matter (SOM), penetration resistance (PR), bulk density (BD), water aggregate stability (WAS), and infi ltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
4
24
0
3
Order By: Relevance
“…According to Zibilske and Bradford [33] and Williams et al [34], zone tillage, e.g., strip-till or ridge tillage, enhances the retention and accumulation of water in topsoil. This is due to the improvement of many physical and chemical properties of soil, e.g., the accumulation of organic matter, the formation of permanent soil structure aggregates [35,36]. In the present research, a higher water content in soil, both in autumn and spring-summer winter wheat vegetation, was found for ST technology.…”
Section: Discussionsupporting
confidence: 50%
“…According to Zibilske and Bradford [33] and Williams et al [34], zone tillage, e.g., strip-till or ridge tillage, enhances the retention and accumulation of water in topsoil. This is due to the improvement of many physical and chemical properties of soil, e.g., the accumulation of organic matter, the formation of permanent soil structure aggregates [35,36]. In the present research, a higher water content in soil, both in autumn and spring-summer winter wheat vegetation, was found for ST technology.…”
Section: Discussionsupporting
confidence: 50%
“…The yield reduction in no‐till relative to strip‐till in our study is possibly due to the cooler and wetter soil conditions from no‐till in early spring, which may contribute to delayed emergence and yield reduction (Buman, Alesii, Hatfield, & Karlen, 2004). Another possible explanation may be attributed to enhanced nutrient uptake, soil organic matter, water use efficiency, water filtration, and water storage capacity with strip‐till relative to no‐till (Fernández & White, 2012; Fernández et al., 2015; Lipiec, Kuś, Słowińska‐Jurkiewicz, & Nosalewicz, 2006; Liu, Zhang, Yang, & Drury, 2013; Messiga et al., 2012; Ziadi et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Conservation tillage practices like no‐till and strip till have been adopted by many producers to save operational costs, reduce soil erosion, and conserve soil water (Fernández, Sorensen, & Villamil, 2015; Morrison, 2002). The adoption of deep banding of P and K fertilizers for conservation tillage systems has been hypothesized to increase nutrient availability and thus to enhance crop productivity and fertilizer use efficiency (Mallarino & Murrell, 1998; Yin & Vyn, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Decisions regarding tillage and fertilization options are expected to be driven by the economics of regional agronomic systems, but these crop cultural practices have the potential to affect soil properties after long‐term cropping. For instance, Fernández et al (2015) showed that improved nutrient uptake efficiency and yields with different tillage systems were partially due to improved soil organic matter, bulk density, and penetration resistance. However, data are limited on the effect of long‐term tillage and N fertilization on claypan soil properties.…”
mentioning
confidence: 99%